The Potential of Cassava Processing as an Alternative Food Diversification Substitute for Rice - Pamungkas, Sahril Dwi; Pratiwi, Dila Intan; Rahmadani, Pradiva Afthurrana; Winanto, Asis Riat (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2024)
The price of cassava in raw form is increasingly uncertain, so people choose to process cassava first into cassava crackers. Then, a polemic arose in the community, namely the implementation of business permits and halal certification of food products for MSMEs in the village carried out by the government. Therefore, assistance from the village community in obtaining business permits and halal certification is needed to facilitate the marketing of cassava cracker MSME products owned by the Raman Fajar Village Community. One of the goals is to empower the community so that the community runs to a better condition and as a form of dedication from students through empowerment, training, counseling, guidance, assistance, and exploring the potential that the community can develop. In addition, KKS activities can assist Raman Fajar Village residents in their activities to benefit students. This research was conducted to ensure that all stages of production, raw materials, and manufacturing processes meet the established halal standards. The results show that the implementation of halal certification is booming, increasing consumer confidence and opening up new market opportunities for cassava cracker products. This community service is a real form of contribution to business partners by providing halal certification and labels that are ready to be attached to the packaging.